The mapmakers eaudiobook - Merchant, Tamzin (Hatmakers, 2022)
Return to Cordelia Hatmaker’s spellbinding world of magic and millinery in this sparkling sequel to The Hatmakers . Cordelia Hatmaker has saved England from war. She stopped Lord Whitloof’s sinister plans, rescued the King and Princess, and restored the Makers Guild. But she still hasn’t found her missing father. Ever since Cordelia discovered the hidden map in her father’s telescope, she’s been searching the streets of London by starlight, trying to uncover its secrets. She never expects to stumble upon a secret society of Mapmakers―or to learn that magic isn’t limited to the few Maker families, but instead is all around, if you know where to look. But danger is lurking around every corner, and Cordelia must convince the rival Maker families to work together for once―not only to bring her father home, but to save the very essence of magic itself. . . . With exceptional and inventive storytelling and a lionhearted heroine, Tamzin Merchant once again draws readers into her captivating London and takes them on a breathless new adventure full of wildness, wit, warmth―and magic. Artwork © Paola Escobar, 2020. Published by arrangement with Random House Children’s Publishers UK, a division of The Random House Group Limited.